Age-Based Demography of Two Parrotfish and a Goatfish from Saipan, Northern Mariana Islands - Cassandra Pardee; John Wiley; Brett M. Taylor (Fishes, 2025)
The age-based life history of two commercially important parrotfishes (Labridae: tribe Scarinae) and one goatfish (Mullidae) were characterized based on the commercial nearshore fishery in Saipan, Commonwealth of the Northern Mariana Islands. Age, growth, reproduction, and mortality were derived from fishery-dependent samples using sagittal otoliths and gonads for the stareye parrotfish Calotomus carolinus, pacific bullethead parrotfish Chlorurus spilurus, and yellowfin goatfish Mulloidichthys vanicolensis. All three species had short lifespans of 10 years or less, with a maximum age of 4 years for C. carolinus, 10 years for C. spilurus, and 7 years for M. vanicolensis. All three species had a fast initial growth to terminal body sizes, early maturation, and spawned throughout the year. The age-based demographic information presented here can be used to inform future stock assessments, fisheries management, and population models.